Otonomi Daerah dalam Pengembangan Kesejahteraan Sosial Anak Terlantar di Kota Serang Berdasarkan Undang-Undang Nomor 23 Tahun 2014 - Endayani; Try Adhi Bangsawan; Maulana Suprihatin; Ahmad Mi Roji; Muhamad Rendiyani (Pusat Riset dan Inovasi Nasional, 2023)
Children are national assets who have the right to grow and develop optimally. Living on the streets is very dangerous for children. The aim of the research is to determine the application of the principle of regional autonomy in developing social welfare for neglected children and the obstacles in overcoming the problems of abandoned children in Serang City. The research uses qualitative methods with a case study approach. This research concludes that the Regional Government of Serang City, in implementing the principle of regional autonomy for the welfare of neglected children based on Law Number 23 of 2014, has the authority to make regional policies that have an impact on prosperity and general welfare in its region. The Serang City Government is responsible for providing social services to neglected children by providing children's rights and protecting them from the risks and threats of life on the streets. The obstacle to handling the problem of abandoned children is the mindset of abandoned children and families which are still oriented towards financial conditions as the main reference, thereby ignoring risks and other threats of danger. Problems with the level of education, habits of abandoned children and limited budgets provided also become obstacles to the implementation of handling abandoned children..